2016
DOI: 10.1007/s10530-016-1159-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genetic diversity of two invasive Pissodes spp. Germar (Coleoptera: Curculionidae) in their introduced range in the southern hemisphere

Abstract: Department, Uruguay) are acknowledged for providing dead insect specimens. We also thank the two anonymous reviewers for their constructive suggestions and comments. AbstractDuring the first half of the twentieth century, two accidental cases of introduction of Pissodes weevils were recorded from the southern hemisphere. The weevils in South Africa were identified as the deodar weevil (Pissodes nemorensis) and those in South America as the small banded pine weevil (Pissodes castaneus). Wide distribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…It can be particularly harmful for nurseries, as the adults feed on seedlings (Ollieu, 1971). In addition, it vectors Fusarium circinatum, the causal agent of pitch canker, and Leptographium procerum, the causal agent of procerum root disease (Wondafrash et al, 2016).…”
Section: P Nemorensismentioning
confidence: 99%
See 1 more Smart Citation
“…It can be particularly harmful for nurseries, as the adults feed on seedlings (Ollieu, 1971). In addition, it vectors Fusarium circinatum, the causal agent of pitch canker, and Leptographium procerum, the causal agent of procerum root disease (Wondafrash et al, 2016).…”
Section: P Nemorensismentioning
confidence: 99%
“…Its only known host is of high economic value, being used as Christmas trees (O'Brien, 1989a). (Wondafrash et al, 2016) and, in any case, the likelihood of finding a suitable host is very high in the whole of the EU.…”
Section: P Zitacuarense Pinus Ayacahuitementioning
confidence: 99%
“…The association with F. circinatum has also been shown in South Africa, where the beetle has been introduced and causes increasing damage on Pinus radiata plantations, mainly through the destruction of terminal leaders. However, recent molecular studies suggest that this species is not P. nemorensis , but an unrecognised species of the P. strobi complex or a hybrid between P. strobi and P. nemorensis (Wondafrash et al., ). Pissodes fasciatus attacks dead or dying stems of Douglas‐fir, Pseudotsuga menziesii , which in itself is not of economic importance. However, Witcosky et al.…”
Section: Pest Categorisationmentioning
confidence: 99%
“…was first detected in South Africa in 1942 and identified as the deodar weevil Pissodes nemorensis Germar, a native to North America (Webb, ; EPPO, ). Recent research, however, has shown that it is not the deodar weevil but rather an unrecognized species of the P. strobi complex of North American origin (Wondafrash et al , ). As with other members of the genus, Pissodes sp.…”
Section: Introductionmentioning
confidence: 99%
“…Based on literature and field observations, the woodwasp appears to prefer moderately stressed trees that are alive and standing at the time of attack (Bordeaux & Dean, ; Ryan & Hurley, ). By contrast, the weevil larvae and pupae are primarily found in severely declining or recently dead trees, including downed trees (Gebeyehu & Wingfield, ; Wondafrash et al , ). The degree to which the attack behaviour of S. noctilio provides a breeding habitat that would have otherwise been unavailble to Pissodes sp.…”
Section: Introductionmentioning
confidence: 99%